The Influence of Online Customer Reviews and Promotions on Purchase Intentions of Wardah Cosmetic Products on Shopee in Surabaya - Mawardhany, Shelomitha Kumala; Soebiantoro, Ugy (Formosa Journal of Multidisciplinary Research, 2025)
Skin and body care products are increasingly important to support appearance, driving the growth of the cosmetics industry in Indonesia. One of the popular brands is Wardah. Shopee, as the most popular marketplace in Indonesia, offers the convenience of contactless shopping and practical payment methods. This study aims to analyze the influence of Online Customer Review (OCR) and promotions on purchasing interest in Wardah cosmetics on Shopee Surabaya. Data were collected through a Google Form questionnaire with a non-probability sampling method and involved 100 respondents. Data analysis used the bootstrapping method with SMARTPLS 3. The results show that OCR and promotions have a positive effect on purchasing interest in Wardah cosmetic products on Shopee.